2016
DOI: 10.1002/9781119165156.ch5
|View full text |Cite
|
Sign up to set email alerts
|

First‐Passage Processes in Cellular Biology

Abstract: We first review fundamentals of the theory of stochastic processes. The system dynamics are specified by the set of its states, {S}, and the transitions between them, S → S , where S, S ∈ {S}. For example, the state S can denote the position of a Brownian particle, the numbers of molecules of different chemical species, or any other variable that characterizes the state of the system of interest. Here we restrict ourselves to processes for which the transition rates depend only on the system's instantaneous st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
85
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 192 publications
(299 reference statements)
0
85
0
1
Order By: Relevance
“…There is already a rich tradition of using such FPT approaches to study timing of events in biological and physical sciences (22)(23)(24)(25)(26). Following this tradition, exact analytical expression for the FPT distribution is computed in experimentally validated and commonly used stochastic models of gene expression.…”
mentioning
confidence: 99%
“…There is already a rich tradition of using such FPT approaches to study timing of events in biological and physical sciences (22)(23)(24)(25)(26). Following this tradition, exact analytical expression for the FPT distribution is computed in experimentally validated and commonly used stochastic models of gene expression.…”
mentioning
confidence: 99%
“…This is consistent with the observation that often, the effect of chemotherapy on recurrence rates does not last for a long time after chemotherapy ends. Several clinical trials [23][24][25] have shown that improved recurrence rates for patients receiving chemotherapy revert to rates for the control group (who received no chemotherapy) in a relatively short time after termination of treatment, suggesting the presence of residual 45 dormant tumor foci that survive treatment and regenerate the cancer. These data also suggest that shortduration chemotherapy only targets the tumor foci that cycle during chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The backward Kolmogorov approach is often more appropriate to first-passage time problems [45][46][47][48] and will be used in combination with Eq. (15) to derive an equation for S(t).…”
mentioning
confidence: 99%
“…Some of these processes require the precision in the timing that regulatory 461 proteins reach thresholds, e.g., control of cell cycle, whereas the others depend on the 462 time that regulatory proteins reach a threshold level (i.e., arrival time), e.g., apoptotic 463 cells showed a faster accumulation of p53 than surviving cells and a shorter time to 464 reach half-maximal p53 levels. Previous studies focused on precision in the timing of 465 events in response to a fixed threshold [34][35][36][37][38][39][40]. However, the thresholds that biochemical 466 events cross are in general dynamically fluctuating, as interpreted in the introduction.…”
mentioning
confidence: 99%
“…Such 29 a kind of threshold has a strong biological background and is ubiquitous in biological 30 regulatory systems. For example, consider a representative activity function of Hill 31 type [33][34][35][36] 32 Activation = Z n Z n + K n (1) first-passage properties of stationary threshold crossing [34][35][36][37][38][39][40], while comparatively very 42 few studies have investigated how a dynamically fluctuating threshold impacts timing 43 precision and arrival time theoretically [41][42][43][44] or experimentally [9,12,26]. 44 In this article, we formulate the timing of intracellular events as a first passage 45 time (FPT) problem, where an event is triggered when a stochastic process (in fact 46 single-cell protein level) crosses a dynamically fluctuating threshold for the first time.…”
mentioning
confidence: 99%